DOP17 HIV infection is associated with a less aggressive phenotype of inflammatory bowel disease. A multicenter study based on the ENEIDA registry. (30th January 2023) - Calafat Sard, M; Súria, C; Mesonero, F; de Francisco, R; Yagüe Caballero, C; de la Peña, L; Hernández-Camba, A; Marcè, A; Gallego, B; Martín-Vicente, N; Rivero, M; Iborra, M; et al.
Abstract: Background: The coexistence of immune-mediated diseases and non-pharmacological immunosuppression states are rare and might determine the natural history of the disease and therapeutic decisions of the physician. IBD guidelines recommend screening for human immunodeficiency virus (HIV) before starting immunosuppressive treatment, but data on the impact of HIV infection on IBD and its management in the era of biological drugs are scarce. Therefore, our aim was to describe IBD phenotype, immunosuppressive requirements, and prevalence of opportunistic infections (OI) in patients with IBD and coexistent HIV infection. Methods: Case-control, retrospective, multicenter study including all IBD patients with available HIV serology on the ENEIDA registry (a large, prospectively maintained database of the Spanish Working Group in IBD –GETECCU). IBD patients with positive HIV serology were selected (HIV+) and compared to HIV seronegative IBD patients (controls), matched 1:3 by year of IBD diagnosis, age, gender and type of IBD). Demographic, clinical IBD characteristics, therapeutic requirements, OI and IBD complications were registered. Results: Eighty-eight HIV+ IBD patients and 264 controls were included. In the whole cohort, 81% were men, 56.8% had ulcerative colitis (UC), 36.4% Crohns' disease (CD) and 6.8% IBD unclassified. Median age at IBD diagnosis was 38 years (IQR 30-47), median age at HIV infection diagnosis was 36 years (IQR 30-42), 46.3% being were firstly diagnosed of IBD. Among UC patients, HIV+ had a lower proportion of extensive disease (24.5% vs 44.8%; P=0.002), and a higher proportion of proctitis (38.8% vs. 16.6%; P=0.002) than controls, without differences on disease proximal progression (7.7% vs 7.9%). Among CD patients, HIV+ presented a higher proportion of colonic involvement than controls (40.6% vs 12, 6%, P=0.002) and lower penetrating behavior (10.7% vs 25%; ns). HIV+ had a lower proportion of extraintestinal manifestations (10.7% vs 25.4%; P=0.005). Although it was not statistically significant, a trend towards a lower proportion of hospitalizations (25.6% vs 35.3%) and IBD complications (6.3% vs. 9.2%) in HIV+ was observed. Regarding IBD therapeutic requirements, immunosuppressant (40.5% vs 58.7%; P=0.003) and biological drugs (28.3% vs 42.8%; P=0.020) were used less frequently among HIV+ than among controls. Conversely, HIV+ had a higher rate of OI (38.3% vs 17.8%; P<0.001) and malignancies (12.5% vs 8.3%, ns) than controls. Conclusion: The coexistence of IBD and HIV infection seems to be associated with a less aggressive IBD phenotype and a lower use of immunosuppressants and biologicals but with a remarkable rate of OI.